President Bolsonaro’s Promises and Actions on Corruption Control - Paul Lagunes; Gregory Michener; Fernanda Odilla; Breno Pires (Revista Direito GV)
Abstract Before the 2018 Brazilian presidential elections, candidate Jair Bolsonaro offered a bold message on corruption control. Among his promises, Bolsonaro vowed to promote government transparency, dismiss any member of his team accused of corruption, and defend the country’s institutions of accountability. Bolsonaro also offered to support a once-popular legislative reform proposal known as the Ten Measures Against Corruption. However, it is worth cautioning that anticorruption as a rhetorical device has been a near-permanent feature of the Brazilian political landscape. In this article, we seek to compare Bolsonaro’s campaign promises with his early actions as president. The evidence shows that, months after the 2018 elections, President Bolsonaro has failed the anticorruption mandate on which he was elected.